A TECHNICAL ANALYSIS OF THE FUNCTIONAL PRINCIPLES OF PNEUMATIC SEEDING MECHANISMS IN MODERN AGRICULTURAL SEEDERS - I.V. Obichayev (Modern American Journals, 2025)
This article provides a comprehensive analysis of the operational principles of seed metering mechanisms in pneumatic seed drills, which are widely used in modern agricultural engineering. Pneumatic sowing systems utilize vacuum-generated airflow to ensure precise and uniform seed placement, contributing to higher crop yields and efficient energy usage in farming operations. The study explores the structural components and functionality of key units within the seeding mechanism, such as the vacuum fan system, seed distribution chambers, drive wheels, and energy transmission components.Special attention is given to the design configurations developed by the GSKB (State Special Design Bureau) and their integration into the EDX 9000 series seeders. These machines are evaluated in terms of seeding accuracy, operational efficiency, and adaptability to various field conditions. The research highlights the role of mechatronic systems in optimizing seeding performance and reducing material losses during operation.Moreover, the application of pneumatic drills in precision agriculture is discussed, along with their significance in enhancing planting quality in large-scale crop production. The findings suggest that innovations in vacuum-based seed delivery systems can lead to improved planting uniformity and resource efficiency, making pneumatic seeders an essential element in the modernization of mechanized sowing technologies.
Keywords: Pneumatic seed drill, sowing mechanism, vacuum fan system, wheels, energy efficiency, GSKB design, sowing machine, EDX 9000.